Some kind of courage [compact disc, unabridged] - Gemeinhart, Dan (Scholastic Audio, 2016)
In 1890 Washington the only family Joseph Johnson has left is his half-wild Indian pony, Sarah, so when she is sold by a man who has no right to do so, he sets out to get her back--and he plans to let nothing stop him in his quest.